Biodiversity for Food and Nutrition in Brazil - Hunter, D.; Moura de Oliveira Beltrame, Daniela (International Food Policy Research Institute, 2015)
The Biodiversity for Food and Nutrition Project—officially the Mainstreaming Biodiversity Conservation and Sustainable Use for Improved Human Nutrition and Well-being project, or BFN project, is a multi-country initiative with an ambitious goal to mainstream biodiversity conservation to improve nutrition in four countries: Kenya, Sri Lanka, Turkey, and Brazil. In Brazil, the BFN project is just one of many initiatives within a national strategy to eradicate hunger and extreme poverty, specifically by mainstreaming biodiversity into national food and livelihood efforts. The project is influencing the national policy landscape, both by filling critical data gaps through an online portal which will streamline national data on Brazilian biodiversity and ecosystems, and through strong partnerships.